TOTAL PRODUCTIVE MAINTENANCE ANALYSIS FOR A380 PARTS. (A CASE STUDY IN INDONESIAN AEROSPACE MANUFACTURER) - Fadhila, Aldo
PT Dirgantara Indonesia is the only aero plane manufacturer and aerostructure in Indonesia.. To ensure customer satisfaction, PT Dirgantara Indonesia has to produce their products on time and ensure quality assurance for the product. One of the supporting business unit is Spirit Program under the Aerostructure Departement. As of 2017 alone, PT Dirgantara Indonesia’s Spirit Program loss $167.399,00. 73% of the losses are coming from wing parts production for A380. While the rest of the losses came from parts production of A350 and A320. From the business issue, taken from one of the expensive parts of A380 wing parts is the Drive Rib 1. Using root cause analysis by Current Reality Tree it was found that the problem that caused the defect is the unreliability of DGAL Cincinnati Milacron that is used for machining the raw material. Using Total Productive Maintenance framework by calculating the Overall Equipment Effectiveness, it is found that the OEE of the machine is at 50.3% which is under the industry standard. Knowing the root cause, the alternative solution from the Total Productive Maintenance Pillar that proposed is Autonomous Maintenance, Quality Maintenance and Machine replacement. The simulated OEE results for the alternative solution are 57.85% for autonomous maintenance, 53% for quality maintenance and 67.1% for Machine Replacement. To choose the best alternative solution to reduce loss, Analyitical Hierarchy Process is used on the stakeholders of the program by using three criteria. Through discussion and AHP Questionare it was found that the stakeholders choose Autonomous Maintenance as the best solution to implement in PT Dirgantara Indonesia for short term period. The long term solution choosen is Machine Replacement. Using capital budgeting, the resulting projected NPV is at $457.568,37 and IRR at 10%.